Remodeling Cyber Notary Concept in Making Notarial Deeds Electronically - Berliana, Nadia Shafa Ghalia; Rahma, Sabrina Zahara Noor; Salsabila, Anisa; Basoeky, Unggul (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
Books:Echols, John M., & Hassan Shadily. (2007). An English-Indonesia Dictionary. Jakarta: PT Gramedia Jakarta.Klatt, Matthias. (2008). Making The Law Explicit The Normativity of Legal Argumentation. US and Canada: Hart Publishing.Krisnayudha, Backy. (2016). Pancasila dan Undang-undang: Relasi dan Transformasi Keduanya Dalam Sistem Ketatanegaraan Indonesia. Kencana: Jakarta.Nurita, R., A., Emma. (2012). Cyber Notary Pemahaman Awal Dalam Konsep Pemikiran. Bandung: PT Refika Aditama.M Friedman, Lawrence. (1984). American Law. London: W.W. Norton & Company.Soesatyo, Bambang., & Rina Indiastuti. (2023) Cyber Notary dan Tantangan Notaris di Era Digital. Bandung: PT Refika Aditama.Suteki., & Galang Taufani. (2020). Metodologi Penelitian Hukum (Filsafat, Teori dan Praktik), 3rd ed. Depok: Rajawali Pers.Journals:Alincia, Devi., & Tundjung Herning Sitabuana. (2021). Urgency of Law Amendment as Foundation of The Implementation of Cyber Notary. LAW REFORM, Vol. 17, No. 2: p.214-231. accessed from https://doi.org/10.14710/lr.v17i2.41749Angin, Evi Veronika Perangin-. Juridical Analysis of the Failure of Ratification of Limited Liability Companies due to Interruption of the Online Public Legal Administration System (AHU Online ). p.2. accessed from https://mkn.usu.ac.id/images/20.pdfClarissa, Novia Betsy Clarissa & Siti Malikhatun Badriyah. (2023). Efektivitas Pendaftaran Jaminan Fidusia Secara Online oleh Notaris. Jurnal Notarius. Vol. 16, No. 1 : p. 428 accessed from https://ejournal.undip.ac.id/index.php/notarius/article/download/41927/pdfKhadafi, Muammar., Iskandar Muda, & Irwan Santosa. (2023). Implementasi Hukum Prinsip Mengenali Pengguna Jasa Dilaksanakan Notaris Terhadap Pelaporan Transaksi Keuangan Mencurigakan Melalui Aplikasi Go-AML Berdasarkan Peraturan PPATK Nomor 3 Tahun 2021. Jurnal Hukum dan HAM Wara Sains Vol. 02, No. 09: p. 746 accessed from https://wnj.westscience-press.com/index.php/jhhws/article/view/614Legowo, A. (2017). Harmonisasi Pengaturan Pemberian Jangka Waktu Hak Pakai Bagi Warga Negara Asing. Arena Hukum, Vol. 10, No. 1, pg. 97-119. accessed from https://doi.org/10.21776/ub.arenahukum.2017.01001.6Mawar, Sitti. (2016). Metode Penemuan Hukum (Interpretasi dan Konstruksi) Dalam Rangka Harmonisasi Hukum. Jurnal Justisia, Vol.1, No.1, pg. 6. accessed from https://jurnal.ar-raniry.ac.id/index.php/Justisia/article/view/2558Prabu, Nurul Muna Zahra., Endang Purwaningsih, & Chandra Yusuf. (2019). Problematika Penerapan Cyber Notary Dikaitkan Dengan Undang-Undang Nomor 2 Tahun 2014 tentang Perubahan Atas Undang-Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris. Jurnal Surya Kencana Dua: Dinamika Masalah Hukum dan Keadilan Vol. 6, No. 2. p. 878-899. accessed from https://openjournal.unpam.ac.id/index.php/SKD/article/view/3995Prasetya, Dewa Gede Ananta., et.al. (2022). Tinjauan Yuridis Industri E-commerce Dalam Melakukan Kegiatan Transaksi Online. Jurnal Konstruksi Hukum, Vol. 3, No. 2: p. 368 accessed from https://www.ejournal.warmadewa.ac.id/index.php/jukonhum/article/view/4838Primananda, Eko., Wukir Ragil, & Dian Puji Simatupang. (2021). Analisis Penerapan Sistem AHU Online Pada Ditjen AHU, Kemenkumham Republik Indonesia: Suatu Kajian Yuridis Normatif. JURNAL META-YURIDIS, Vol. 4, No. 1: p. 134-135 accessed from https://journal.upgris.ac.id/index.php/meta-yuridis/article/view/7990Widyastuti, Erna Ferika. (2021). Kedudukan Sertipikat Elektronik Sebagai Alat Bukti Dan Tanggung Jawab Pejabat Pembuat Akta Tanah Serta Kantor Pertanahan. Officium Notarium, Vol. 1, No. 3: p. 479 accessed from https://journal.uii.ac.id/JON/article/view/22266/14227Regulation:Civil Code;Law No. 30 of 2004 concerning the Position of Notary;Law No. 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Position of Notary;Electronic Information and Transactions Law;Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions;Regulation of the Minister of Communication and Information of the Republic of Indonesia Number 11 of 2022 concerning Governance of the Implementation of Electronic Certification;Federal Code For Notaries (Bundesnontarordnung - BNotO)(German);Decree 2005 973 of 10/08/2005(French); andNotaries Act(Estonia).Internet:Cabinet Office. “Society 5.0”. https://www8.cao.go.jp/cstp/english/society5_0/index.html accessed on 22th June 2024. Dinas Penanaman Modal & Pelayanan Terpadu Satu Pintu Provinsi Kepulauan Bangka Belitung. “Sistem OSS” https://dpmptsp.babelprov.go.id/node/1106, accessed on 22th June 2024.E-Estonia. “E-Residency dibentuk untuk mempermudah transaksi dan kegiatan bisnis across border”. https://e-estonia.com/wp-content/uploads/faq-e-residency-dets2023.pdf accessed on 25th June 2024.Hukumonline. “Kedudukan KUH Pidana dan KUH Perdata dalam Hierarki Peraturan Perundang-undangan”.https://www.hukumonline.com/klinik/a/kedudukan-kuh-pidana-dan-kuh-perdata-dalam-hierarki-peraturan-perundang-undangan-lt4f1e71d674972/ accessed on 21th June 2024.__________. “Kedudukan Peraturan Menteri dalam Hierarki Peraturan Perundang-undangan”.https://www.hukumonline.com/klinik/a/kedudukan-peraturan-menteri-dalam-hierarki-peraturan-perundang-undangan-lt5264d6b08c174/ accessed on 21th June 2024.Kamus Besar Bahasa Indonesia. “Disharmoni”. https://kbbi.kemdikbud.go.id/entri/disharmoni accessed on 21th June 2024.Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional. “Kompilasi Data Hak Tanggungan Elektronik (HT-el)” https://www.atrbpn.go.id/grafik-htel, accessed on 22th June 2024.Techtarget. “What is artificial intelligence (AI)? Everything you need to know”. https://www.techtarget.com/searchenterpriseai/definition/AI-Artificial-Intelligence#: :text=Artificial%20intelligence%20is%20the%20simulation,by%20machines%2C%20especially%20computer%20systems, accessed on 24th June 2024.Oxford Learner’s Dictionaries. “remodel” https://www.oxfordlearnersdictionaries.com/definition/english/remodel?q=remodel, accessed on 22th June 2024.Other:Basoeky, Unggul. (2022). Rekonstruksi Politik Hukum Kenotariatan Untuk Mewujudkan Harmonisasi Hukum Terhadap Kewenangan Notaris di Era Revolusi Industri 4.0. [Doctoral dissertation, Diponegoro University].Seminar:Adjie, Habib. “UU No. 1 Tahun 2024 Tentang ITE, Transformasi Digital & Cyber Notary”. National Seminar of Universitas Padjadjaran, 01 March 2024.